Pengaruh Kinerja Karyawan dan Kualitas Pelayanan terhadap Kepuasan Pengunjung pada UPPD Banjarmasin II - Rida Astuti (P3M Politeknik Negeri Banjarmasin, 2023)
UPPD Banjarmasin II is one of the companies engaged in public administration services and identification of motorized vehicles. The purpose of this study was conducted (1) To determine whether employee perfomance and service quality had simultaneously influence visitor satisfaction at UPPD Banjarmasin II. (2) To find out whether the perfomance of employees partially influences the satisfaction of visitors at UPPD Banjarmasin II. (3) To find out whether the quality of service has partially influence the satisfaction of visitors at UPPD Banjarmasin II. This study uses a quantitative descriptive method. The population used is the number of visitors in the last 5 years by 799,510 with a number of samples taken as many as 100 respondents. The analysis technique used is a multiple linear regression analysis technique. The results of this study show that: (1) Employee Performance variables (X1) and service quality (X2) Have simultaneously influence visitor satisfaction (Y) at UPPD Banjarmasin II with the value of Fcount (19,564)> Ftable (3.09). (2) The Performance Variable Employee (X1) does not have a partial effect on visitor satisfaction (Y) at UPPD Banjarmasin II by comparing the value of Tcount (0.106) < Ttable (1.98). (3) Service Quality Variables (X2) Have partially influence on visitor satisfaction (Y) at UPPD Banjarmasin II by comparing the value of Tcount (4.915)> Ttable (1.98).